What We Do in the Shallows: Natural and Anthropogenic Seafloor Geomorphologies in a Drowned River Valley, New Zealand - Watson, Sally J.; Neil, Helen; Ribó, Marta; Lamarche, Geoffroy; Strachan, Lorna J.; MacKay, Kevin; Wilcox, Steve; Kane, Tim; Orpin, Alan; Nodder, Scott; Pallentin, Arne; Steinmetz, Tilmann (Frontiers in Marine Science, 2020)
The shallow marine environment represents a region of high biological productivity, ecological diversity, and complex oceanographic conditions, and often supports various human activities and industries. Mapping of the seafloor in shallow marine environments reveals seafloor features in detail, shedding light on a range of natural and anthropogenic processes. We present a high-resolution (2-m) multibeam dataset, combined with geologic samples that reveals a complete map of the seafloor from the land-water interface to ~350 m water depth within Queen Charlotte Sound/Tōtaranui (QCS) and Tory Channel/Kura Te Au (TC), Marlborough Sounds, New Zealand. These data reveal that the seafloor geomorphology and distribution of natural and anthropogenic features varies spatially from the inner QCS to the Cook Strait. Tidal currents play a large role in the erosion, transport, and deposition of sediments in QCS and TC. The distribution and depth of seafloor scouring suggests that tidal flow is locally intensified by coastal geometry and bathymetric barriers, resulting in concentrated scouring where tidal flow is restricted or redirected. In addition, superimposed bedforms reflect localised variations in flow direction that have likely developed across a range of spatial and temporal scales. Evidence for extensive seafloor fluid expulsion is preserved in >8500 pockmarks mainly located within the inner and central QCS. The size and spatial distribution of pockmarks suggest multiple fluid sources in the region. The cumulative anthropogenic footprint on the seafloor within QCS represents 6.4 km2 (~1.5%) of the total seafloor area and is predominantly related to maritime activities including anchor dragging (47.5%) and mooring blocks (24%). This study provides a unique example of the information that can be revealed by a comprehensive survey programme that mapped from the land-water interface to the subtidal zone. Results presented in this study form a robust basis upon which to develop improved hydrodynamic models and benthic habitat maps and to assess the full extent of anthropogenic activities in the shallow marine realm.